PENGEMBANGAN BUKU SISWA SMP KELAS VIII DENGAN MATERI PRISMA DAN LIMAS YANG BERPIJAK PADA MASALAH KONTEKSTUAL, PENGGUNAAN MODEL, DAN PENEMUAN TERBIMBING - Syarifudin, Syarifudin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
The development of this student book uses the Thiagarajan development model. The development of this model has four stages: definition, planning, development, and dissemination. In addition, the development of students' books is based on realistic mathematics education (PMR), especially on contextual issues, the use of models, and guided discovery. Subsequently the student's book has validated experts and practitioners to be tested in the classroom. Expert and practitioner scores were 3.46 (very valid). Furthermore, it was tested in the classroom in order to see the practicality and effectiveness. Practicality of students' books is measured through the implementation of learning in the learning process. Student book implementation data as a whole is 'high categorized'. Student book effectiveness is measured through three indicators: (1) student activity, (2) student response, and (3) mastery learning. Through classroom tests, data on students' activity observation outcomes during the learning process as a whole are 'active criteria'. Students give a positive response. Post-test data found that none of the students scored under 65% of the standard learning objectives to be achieved. Furthermore, if seen classically obtained an average of 83.1%.